Management of Students Professional Competencies Formation on the basis of Interdisciplinary Integration - Rapatskaia, Liudmila A.; Alekseeva, Elena V.; Vorontsova, Elvira M.; Konstantinova, Valentina V.; Sadykova, Aida G.; Tumarov, Konstantin B.; Streltsova, Anna S.; Timirov, Fedor F. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the modernization of professional training the leading strategy of which is the formation of professional competencies. Professional education is characterized by the desire to overcome the professional isolation and to develop a more democratic and effective professional training systems focused on competitive creative professional. The purpose of the article is to provide a control mechanism for the formation of professional competencies of future specialists on the basis of interdisciplinary integration. The leading method has become the method of action research (AR), which allows gaining of new knowledge about the future specialists' professional training, focused on the formation of entity-entity relations, personal meanings and life values on the basis of interdisciplinary integration. The article reveals leading trends in the development of future specialists' professional training (reforming, accessibility, solidity and continuity); structure-forming components of professional competencies are allocated (epistemological, normative and functional); the peculiarities of future specialists' professional competencies formation on the basis of interdisciplinary integration are clarified (focus on holistic education throughout life; upbringing of sustainable civil qualities of the person; the relationship of academic disciplines, ensuring complementarities of content, forms, methods and means of professional training and the creation of common educational modules for various logical reasons); the idea of case-method implementation in the training process is suggested. The paper submissions can be useful for teachers of research universities; centers to enhance personnel training and retraining while selecting and structuring of the content for professional development of the research universities' teaching staff. Keywords: Interdisciplinary Integration, Professional Competence, Professional Training, Case Method. JEL Classifications: A23, I23, I26